Highlights of the results from the GRAPES-3 experiment - Balakrishnan, Hari Haran; Ahmad, S.; Chakraborty, M.; Dugad, S. R.; Goswami, Umananda Dev; Gupta, S. K.; Hayashi, Y.; Jagadeesan, P.; Jain, A.; Jain, P.; Kawakami, S.; Kojima, H.; et al. (SciPost Physics Proceedings, 2023)
The GRAPES-3 experiment is a unique, extensive air shower experiment consisting of 400 scintillator detectors spread over 25000 m ^2 2 and a 560 m ^2 2 muon telescope. The experiment located at Ooty, India, has been collecting data for the past two decades. The unique capabilities of GRAPES-3 have allowed the study of cosmic rays over energies from a few TeV to tens of PeV and beyond. The measurement of the directional flux of muons (E _μ μ ≥1 GeV) by the large muon telescope permits an excellent gamma-hadron separation, which then becomes a powerful tool in the study of multi-TeV gamma-ray sources and the composition of primary cosmic rays. However, the high precision measurements also enable studies of transient atmospheric and interplanetary phenomena such as those produced by thunderstorms and geomagnetic storms. This paper presents some exciting new and recent results, including updates on various ongoing analyses.